Analisis Pengaruh Brand Equity Dan Content Marketing Melalui Media Sosial Terhadap Keputusan Pembelian Produk Wardah di Kota Medan - Aulia Saragih, Mazra; Sinambela, Nova; Hanifah, Nayla; Khairani, Anisya; Clearinkris, Junesia; Marakali Siregar, Onan; Mulyati Siregar, Afrila (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2024)
The very rapid development of technology has caused changes in various fields, one of which is business, various ways are used by companies to market their products, starting from building good brand equity to creating content via social media. The population of this research is people in Medan City who use Wardah products with a total sample of 100 respondents who have purchased Wardah products. From the data collected, data analysis was carried out using SPSS to determine the results of the research hypothesis. The results of this research show that brand equity and marketing content through social media can influence the purchasing decisions that a consumer will make, which means that the stronger the brand equity and the more interesting the content used in marketing, the greater the customer's purchasing decisions can be.